Leading issues in economic development - Meier, Gerald M.; Rauch, James E. (New York : Oxford University Press, 2000)
Economics
Keywords: Economic development; Savings; Investment; International trade; Human resources; Migration; Agriculture; Income distribution; Political economy; Environment